Estructuras legales trasformadoras en América Latina en el siglo XXI - De la Barra, Ximena (Universidad de Chile. Programa Domeyko, 2011)
In Latin America, the severe flaws in post dictatorial representative democracies and the constitutional principles originally designed to facilitate the exploitative governments of landed and capitalist elites, begin to be questioned and emerging emancipatory processes point towards the development of participatory democracies. In order to redirect national development the peaceful way, several of these processes have resorted to the transformation of the existing legal order in favour of the dominant classes, redirecting their vision of the future in favour of popular interests. The recovery and transformation of the role of the State and public policies with budget allocation in consonance with the new constitutional and social change projects, become indispensable for the success of these processes. In this scenario, concerted social movement action in the struggle for a post neoliberal future and for liberation regarding imperialist designs, constitute the most powerful force towards change. The recent constitutional processes in Venezuela, Bolivia and Ecuador have benefited from a combination of effective and charismatic popular leaders as heads of government and the pressure from popular bases with demonstrated capabilities for uniting, organizing and mobilizing towards their own agenda towards justice and sovereignty.